Miocene Planktonic Foraminifera of Calcareous Sandstone Unit in Pamutuan Formation West Java, Indonesia (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The research area is located in Cigugur, Jadimulya, and Bangunkarya, Pangandaran, WestJava. This research is focus on identification and determination the age of calcareous sandstone unitbased on foraminifera assemblages. In the research area, the calcareous sandstone unit included inPamutuan Formation. Based on previous research, regionally the age of Pamutuan Formation isMiddle Miocene which deposited with many energy changes and related to the effect of sea levelchanges. The research method started with literature study followed by field observation by usingspotting sampling method, preparation process, and laboratory analysis. Preparation process offoraminifera planktonic performed against six samples of rock by using the method of residues.Samples of foraminifera planktonic are analyzed using binocular microscope and determining theage range of the foraminifera planktonic species based on Bolli classification. The calcareoussandstone unit consists of massive sandstones. The foraminifera planktonic such as Globorotaliaopima nana, Catappsydrax dissimilis, Globorotalia obesa, Globigerinoides ruber, Globorotaliamayeri, Sphaerodinellopsis disjuncta, Globigerinoides obliquus, and Globorotalia fohsiperipheroronda are identified in samples. Based on the presence of those foraminifera planktonicmarker species, conclude that the calcareous sandstone unit in Pamutuan Formation is indicated to bedeposited in the relative age range of N6 to N10 or Early Miocene to Middle Miocene.
Keywords: Foraminifera planktonic; Pamutuan formation; Early Miocene; Middle Miocene